-4=-7(4+c)-18

Simple and best practice solution for -4=-7(4+c)-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=-7(4+c)-18 equation:



-4=-7(4+c)-18
We move all terms to the left:
-4-(-7(4+c)-18)=0
We add all the numbers together, and all the variables
-(-7(c+4)-18)-4=0
We calculate terms in parentheses: -(-7(c+4)-18), so:
-7(c+4)-18
We multiply parentheses
-7c-28-18
We add all the numbers together, and all the variables
-7c-46
Back to the equation:
-(-7c-46)
We get rid of parentheses
7c+46-4=0
We add all the numbers together, and all the variables
7c+42=0
We move all terms containing c to the left, all other terms to the right
7c=-42
c=-42/7
c=-6

See similar equations:

| -4-5+x=-9+x | | 245.35-x=248.02 | | -2b-1=4-4b-5 | | 9v+(-11)=34 | | -17+8r=17+10r | | X-7+4x-2=20 | | -7y+2(y-8)=-6 | | 6y+7y=26 | | t+ 38= 7 | | 9m+7=–5+6m | | 2/3(4x-5)=2/1-x/2 | | (4z+1)/(3)=11 | | 4x+-13=x+8 | | 0.3333x=250 | | $245.35-x=$248.02 | | 4z+5-z=-7 | | 9h+2=65 | | 3^2x−4=47 | | -n/7=21 | | 23x-5+17x+14=29 | | 2z+13=16 | | -20w+18-2w=-16-20w | | 5q-8q=15 | | 0.75x+2-1/3x=12 | | 4.6+10m=6.24 | | 3(y–4)+5y=12 | | 2+14a`=-8+9a | | 52-x=180 | | =(x-3)•(-100) | | 8b+40=-5(-8b+8)+8b | | -2v+9=-5-4v | | f+7/10=9 |

Equations solver categories